Exploring Inter-partner Fit of Malaysian Offshore International Joint Ventures: A Cluster and Discriminant Analysis - Seng, Tey Lian; Heong, Quah Chee (International Review of Management and Marketing, 2016)
This paper aims to classify firms with international joint ventures into distinctive grouping with respect to their degrees of inter-partner fit. It applies cluster and discriminant analysis on the dimensions associated to inter-partner fit amongst Malaysian firms which engage in international joint ventures. The respective dimensions are strategic fit, organisational fit, inter-partner relations fit, national culture fit, and organisational culture fit. Hierarchical cluster analysis indicates four groupings of firms with different extents of conformity to the criteria whilst discriminant analysis signifies strategic fit, inter-partner relations fit, and organisational culture fit as predominant facets that demarcate the firms. The findings are significant in the sense that each of the firms can better understand its position vis-Ã -vis the rest of the firms and hence make necessary adjustments that need improvement. In addition, since strategic fit, inter-partner relations fit and organisational culture fit are more important in distinguishing one firm from another, firms can gain greater efficiency by just concentrating on these facets in their strategic plans. Keywords: Inter-partner fit; Cluster analysis; Discriminant analysis; International joint venture JEL Classification: M16